사무소건물의 LED조명기구 방열장치의 성능 분석 연구 - 덕트 내 유량변화 중심으로 - 박지우; 안병립; 김종훈; 정학근; 장철용; 송규동; Park, Ji-Woo; Ahn, Byung-Lip; Kim, Jong-Hun; Jeong, Hak-Geun; Jang, Cheol-Yong; Song, Kyoo-dong (KIEAE Journal, 14(6), 2014)
In recent years, many researchers have considered the building energy consumption reduction accordingly to deal with abnormal climate changes and greenhouse gas reduction. However, the lighting energy use ratio has increased in spite of the development of the high efficiency lighting device. Therefore, the study aims to produce the LED lighting applications for the effective lighting heat removal by using the heat characteristics of LED lighting and analyzing the heat removal effect. In order to increase radiant heat efficiency, the heat pipe and heat sink was attached on PCB as LED lighting applications. Experiment was conducted to verify the temperature and air velocity of inside duct: thermocouples, anemometer. The heat removal effect of LED lighting applications was measured by observing the temperature of the lighting applications and the change of air velocity in duct. The experiment shows that the temperature change in the duct according to air velocity was $0.9{\sim}5.8^{°}C$. It is also concluded that heat removal was calculated from 33 to 81W.